Analisis Penerapan Struktur Tiga Babak Teori Aristoteles dalam Skenario Film “Key” untuk Meningkatkan Suspense - Amanda Bayu Fadhilah; Dani Manesah (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
This study examines the application of the three-act structure based on Aristotle's theory in the screenplay of the film “Key” to effectively build suspense. The three-act structure—comprising setup, conflict development, and resolution—is a classical narrative framework widely used in filmmaking. The research employs a descriptive-qualitative approach with a case study on the screenplay of “Key.” This study contributes to the development of screenwriting techniques, particularly for genres that prioritize suspense, and provides practical guidance for screenwriters in crafting stories capable of influencing the audience's emotions. The analysis results show that the application of Aristotle's elements in the three-act structure creates a progressive storyline, strengthens the emotional connection between the audience and the characters, and delivers a climactic emotional peak.